(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
Functional analysis teaching procedures are a subject matter of behavior analysis. In Brazil two graduate programs were established, one at UNESP and one at PUC-SP. The aim of this study was to analyze common or similarities procedures data collection/data analysis of research in order to identify their adequacy to behavioral principles of teaching. Data collection procedures were carried out based on consultation with the curriculum of the chief investigator and libraries website. The results showed that some behavioral principles of learning not covered in both groups, such as the adequacy of training procedures to the baseline repertoires of the participants, and their pace and the steps of learning. Regarding the common principles covered the designation of resources, the promotion of constant responding and proposals for education were observed. As final remarks, it is suggested to follow these principles to improve future researches